Analisis Pengendalian Biaya dan Waktu Pekerjaan Struktur dengan Metode Earned Value (Studi Kasus: Asrama Seminari Montfort Kota Malang) - Atarima , Climensia; Yurnalisdel, Yurnalisdel; Wijaya, Handika Setya (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Planning and controlling costs and time on a project is part of construction project management which is very important. If there are project delays or costs that exceed the plan cost, it will affect the implementation of the work. This research case study was selected for the Montfort Seminary Dormitory Structure Construction Project in Malang City. Researchers only analyzed structural work with a duration of 188 calendar days. The researcher's goal is to find out the projected cost and time of completion of the project against the initial planning. The method used is Earned Value Concept using BCWS, BCWP, ACWP indicators. To see the projection of work in this study using Cost Variance with CV and CPI indicators, for Cost estimates using ETC and EAC. As for Time Variance, using SV and SPI indicators and time estimates using EAC and EAS. The projected total cost of completing the project is IDR 2,203,741,880. After the project bidding, the cost amounted to Rp1,844,162,647, and after the implementation, the actual cost or expenditure cost amounted to Rp. 1,809,802,748. With the remaining funds amounting to IDR 34,359,898. The results of the calculation of CPI (Cost Performance Index) until week 27 => 1. The results of the SPI (Schedule Performance Index) calculation up to week 27 =>1 Good and Efficient Cost Performance and Good Schedule Performance with the Schedule according to the Plan and no delays in project construction work.